DAMPAK PENAMBANGAN EMAS SKALA KECIL TERHADAP KEBERLANJUTAN EKOSISTEM PESISIR DAN SOSIAL-EKONOMI DI DESA PELANGAN, LOMBOK BARAT - Fermana, Rudy; Akhdiyat, Hendra R.; Hadi, Islamul; Aryanti, Evy (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Artisanal and Small-Scale Gold Mining (ASGM) in Pelangan Village, Sekotong District, West Lombok, Indonesia, provides significant economic benefits but poses severe environmental and social challenges. This study aims to identify ASGM practices, operational scales, and distribution patterns while analyzing their impacts on social, economic, and ecological aspects, particularly mangrove ecosystems. Using Sentinel-2 L2A satellite imagery and NDVI analysis to assess mangrove health, combined with a Systematic Literature Review (SLR) following PRISMA guidelines, the research synthesized data from 25 relevant articles published between 2009 and 2024. The findings indicate that ASGM contributes to local income but fosters unsustainable economic dependency, with mercury (Hg) contamination in rivers exceeding WHO thresholds and persistent pollution undermining mangrove functions. Socially, ASGM heightens health risks, including anemia and heavy metal bioaccumulation in local communities. Despite some improvements in mangrove health from 2017 to 2024, significant environmental degradation remains. Mitigation strategies such as biochar application and bioremediation, alongside sustainable resource management and community empowerment, are essential to reducing environmental damage while supporting local livelihoods, aligning with SDG 13 (Climate Action) and SDG 14 (Life Below Water)